الجزاءات الادارية العامة: دراسة مقارنة - العاني, وسام صبار (Journal of Legal Sciences, 2019)
The general administrative sanctions from  the  sanctions ,which  recently  emerged to  confront some of  the  crimes that  do  not deserve  to face criminal  sanctions due  to  the lack of seriousness and  gravity in the eyes of society, but enough to face sanction administrative  general   expectation   administration  without  resorting  to the  judiciary, characterized  by  administrative  sanctions  public  bmatiha  own  are in-  dividual   administrative  decision  issued  by the  administration  punish-     ment   for violation of  certain  laws  and  regulations, which  makes  it  a separate  entity  from  all other  forms  of  sanctions, the  general admin-  istrative   sanctions  (fines  and   confiscation)  of  others  and  sanctions   financial (withdrawal of  the license, stop the  activity, the  closure  of the  facility,  administrative removal, publication  of  the  judgment, expel and keep foreign).